Application of graphic apparatus of c-curves for the analysis and optimization of supercritical cycles of thermotransformers - Kharlampidi, Dionis; Tarasova, Victoria; Kuznetsov, Mikhail; Omelichkin, Sergey (Eastern-European Journal of Enterprise Technologies, 2016)
The method of the generalized analysis and optimization of supercritical cycles, allowing the directed search of the most rational flow diagrams of RM and HP at the stage of predesign development, taking into account the structural and topological features of their equipment was proposed. It is, in fact, unique because it is based on a synthesis of modern methods of thermodynamics, system engineering, and graphic optimization techniques. The main advantage of the method consists in the visual presentation of the results that greatly facilitates the flow diagram selection process in the design of the refrigeration unit, making it formalized and controlled. Introduction of the criterion of complexity to the thermoeconomic analysis allowed identifying a rational complication limit of the flow diagram of the refrigerating machine when the introduction of additional equipment in the flow diagram structure in order to reduce the internal irreversibility in a cycle does not lead to the expected efficiency improvement of the unit. It is proposed to use the graphic apparatus of Ccurves to determine the minimum cost of the design and operation of the system over the entire lifecycle. Introduction of the replacement cost factor to the economic analysis allowed using not the cost of reference fuel on the world market as the variable parameter in the optimization, but the estimated operation time of the unit. This made it possible to make a choice not only in favor of cheap and structurally simple but also complicated twostage flow diagrams. Such an approach shall promote the introduction of efficient expensive technologies of thermotransformation in practice since in this case the contribution of the capital component is offset. It is proposed to use the total equivalent warming impact factor to analyze the environmental indicators of flow diagrams of different complexity using the apparatus of Ccurves.